EFFECT OF ARTIFICIAL DIET ADDED DIFFERENT DOSES OF HERBAL SUPPLEMENTS ON GROWTH AND SURVIVAL RATE OF CATFISH LARVAE (Pangasius hypopthalmus) REARED UNDER IN THE WATER RECIRCULATION SYSTEM - Franz Simanullang; Hamdan Alawi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was carried out for 40 days, from 7 May to 16 June 2019 at the Fish Hatchery and Breeding Laboratory Department of Aquaculture, Faculty of Fisheries and Marine, University of Riau, Pekanbaru. The purpose of this study was to find out the best herbal supplement dose added to artificial diet on growth and survival of catfish larvae (Pangasius hypophthalmus) that are kept for 40 days in an aquarium container size of 30x30x30 cm as many as 12 pieces, filled with water as much as 15 liters/container, densely stocked 2 fish/liter with a water recirculation system.with a water recirculation system.The method used in this study was the experimental method that uses one-factor Completely Randomized Design (CRD) consisting of four treatments with three replications. The treatments in this study were P1 (0 ml / 100 gr artificial feed) significantly different from P2 treatment (2.5 ml / 100 gr artificial feed), P3 (5 ml / 100 gr artificial feed) and P4 (7.5 ml /100 gr artificial feed).The best growth research results was obtained in the treatment of P4 (7.5ml / 100g of feed) with an average growth of absolute weight 0.56 grams, growth of absolute length 3.23 cm, specific growth rate of 11.32% /day,while the best treatment for survival was obtained at P2 treatment (2.5 ml /100g of feed) namely 94.44%.Water quality during the study was temperature ranging from 26-28.80C, pH 6 and DO of 3.5-4.52 ppm.  Keywords : Herbal Supplements, Diet, Catfish Larvae (Pangasius hypopthalmus), Growth, Survival Rate